A Study on Socioeconomic Support Systems and Success Rate of Track and Field Athletes in Inner Mongolia Autonomous Region, China - Gao, Erlong (Pacific International Journal, 2024)
This study investigates the correlation between socioeconomic support systems and the success rates of track and field athletes in the Inner Mongolia Autonomous Region of China. Utilizing both primary and secondary data, the research explores the role of governmental programs, educational institutions, family and community support, and financial aid in shaping athletic performance. The findings reveal a strong correlation between robust socioeconomic support and higher athletic success, with significant disparities observed between regions with varying levels of resources. The study identifies key challenges, including inadequate funding and uneven resource distribution, and proposes opportunities for improvement through increased investment, stakeholder partnerships, and enhanced community involvement. Recommendations are made to guide policy and practice towards more equitable support systems, aiming to nurture athletic talent across all socioeconomic backgrounds.